Evaluating clinical characteristics and neuroimaging indications of paediatric traumatic brain injury patients using Scandinavian paediatric traumatic brain injury guidelines in Southwest Finland - Erkinjuntti, Nina; Posti, Jussi P.; Lähdesmäki, Tuire (Elsevier, 2026)
Introduction
Neuroimaging of paediatric head injuries has increased during the past decades.
Research question
To describe clinical features and neuroimaging outcomes of the retrospective cohort, and to assess the alignment of neuroimaging decisions for paediatric head injuries with the Scandinavian guidelines for the management of mild and moderate head trauma in children (SCN16 guideline) in a tertiary care setting.
Materials and methods
Patients <16 years with head injury and neuroimaging were identified through diagnostic registry search at Turku University Hospital (2010–2016), Finland. Medical records were reviewed for data collection. The SCN subgroup included patients assessed within 24 h and with a Glasgow Coma Scale (GCS) of 13–15.
Results
Of the 637 patients (58% male, mean age 9.3 years), traumatic intracranial pathologies were found in 9% (n = 55) on CT and 13% (n = 85) on MRI; 3% (n = 16) underwent neurosurgery. Most skull fractures (82%, n = 31) co-occurred with intracranial findings. Between 2010 and 2016, CT use increased from 37 to 70 and MRI from 20 to 93, while traumatic abnormalities remained stable or decreased. 512 patients were included in the SCN subgroup (59% male, mean age 9.4). Acute neuroimaging was performed in 75%; 91% fulfilled the SCN16 neuroimaging criteria. Two (0.4%) of 163 discharged patients required neurosurgery, and 14 (3%) had traumatic pathology on later neuroimaging.
Discussion and conclusions
In this cohort, neuroimaging indications during 2010–2016 largely aligned with the SCN16 guidelines. Clinical features, neuroimaging utilization, and neurosurgical intervention rates were generally consistent with previous literature.